Clinical practice guidelines for videofluoroscopic swallowing studies: A systematic review. Issue 2 (May 2020) - Boaden, E.; Nightingale, J.; Bradbury, C.; Hives, L.; Georgiou, R.
Abstract: Introduction: Clinical practice guidelines (CPGs) are expected to make evidence-based recommendations, thus guiding practice and reducing unwarranted variation. CPGs are particularly helpful in guiding complex procedures such as the Videofluoroscopic Swallowing Study (VFSS) for the assessment of dysphagia, but there is a suspected high level of variability among them. To explore the extent of this variation, this study aimed to systematically identify and appraise all VFSS CPGs available worldwide. Methods: A systematic search of 3 academic databases and other sources was conducted to identify relevant CPGs; independent reviews of each CPG were undertaken by a Speech and Language Therapist and a Radiographer. Both reviewers completed a pre-determined checklist of expected professional content for each CPG. CPGs were then assessed for quality using the Appraisal of Guidance for Research & Evaluation II (AGREE II) instrument. Findings from the professional content review and the methodological quality review were synthesised to inform an assessment of suitability of each CPG to inform clinical practice. Results: Seven VFSS CPGs were identified worldwide, none of which were co-designed by radiographers or aimed at a radiographer audience. Each differs in their professional content, recommendations, underpinning evidence base and professional focus. Average AGREE ll scores across the quality domains vary considerably, ranging from 93 to 22%. No CPGs scored highly on all six AGREE II domains. Conclusion: There is no standardisation between VFSS guidelines. Six CPGs are not recommended for clinical use; only one of the seven identified CPGs is recommended for use following significant modification. Implications for practice: The lack of a comprehensive, evidence-based guideline encourages unwarranted variation in clinical practice which potentially compromises clinical care. Further research is needed to define VFSS best practice.